Insights into linguistic performance: investigating pragmatic and syntactic violations of Hebrew definiteness through acceptability judgment and self-paced listening and reading tasks - Plaut-Forckosh, Dana; Meir, Natalia (Applied psycholinguistics, 2025)
The current study examined speakers’ performance in identifying syntactic and pragmatic violations of definiteness use across four types of tasks: (1) a reading acceptability judgment task, (2) an auditory acceptability judgment task, (3) an online self-paced reading task, and (4) an online self-paced listening task. This investigation aimed to clarify how methodological differences and similarities within psycholinguistic research might influence linguistic performance in adult speakers. The four experiments focused on pragmatic and syntactic violations of definiteness in Hebrew in both subject and object positions. Overall, participants detected definiteness violations across different modalities and tasks, but notable differences emerged among the tasks. For instance, in the self-paced listening task, sentences with no violations and those with pragmatic violations were indistinguishable, while slower response times were observed exclusively for syntactic violations in the object position. These performance variations may stem from the phonological reduction of the definite article in spoken Hebrew, coupled with online measurement methods that may have led to shallower processing and an increased likelihood of violation overlooking. Alternatively, participants in the online self-paced reading task exhibited the strongest effects in identifying both syntactic and pragmatic violations, indicating that task type and stimulus representation can significantly influence linguistic performance.